2019
DOI: 10.1016/j.ophtha.2019.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Primary Selective Laser Trabeculoplasty for Open-Angle Glaucoma and Ocular Hypertension

Abstract: on behalf of the Laser in Glaucoma and Ocular Hypertension Trial Study Group* Purpose: To report clinical efficacy, predictors of success, and safety of primary selective laser trabeculoplasty (SLT) used in treatment-naive patients with open-angle glaucoma (OAG) or ocular hypertension (OHT). Design: Post hoc analysis of a multicenter, prospective, randomized, controlled trial. Participants: Treatment-naive patients with OAG or OHT. Methods: Patients randomized to SLT or topical medication and treated to predef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 37 publications
(45 reference statements)
4
33
0
Order By: Relevance
“…Heijl et al concluded that the effect can best be predicted by the preoperative IOP level and showed that higher IOP before ALT was associated with greater IOP reduction following topical treatment (Heijl et al 2011). This finding has also been described by others (Chun et al 2016;Pillunat et al 2016;Garg et al 2019). However, most of those studies included eyes with elevated IOP levels prior to LTP and which were in need of additional IOP reduction.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Heijl et al concluded that the effect can best be predicted by the preoperative IOP level and showed that higher IOP before ALT was associated with greater IOP reduction following topical treatment (Heijl et al 2011). This finding has also been described by others (Chun et al 2016;Pillunat et al 2016;Garg et al 2019). However, most of those studies included eyes with elevated IOP levels prior to LTP and which were in need of additional IOP reduction.…”
Section: Introductionmentioning
confidence: 73%
“…Laser trabeculoplasty (LTP) is a wellknown method to reduce the intraocular pressure (IOP) in open-angle glaucoma (OAG). Sometimes, it is used as a first-line treatment (Tuulonen et al 1987;The Glaucoma Laser Trial Research Group 1990;Melamed et al 2003;McIlraith et al 2006;Shazly et al 2010;Garg et al 2019), but more commonly it serves as a supplement to topical IOP-lowering medication (Samples et al 2011;Pillunat et al 2016). Traditionally, argon laser trabeculoplasty (ALT), a method originally comprising argon laser but more recently a diode laser, has been more frequently used (Wise & Witter 1979;Chung et al 1998;Samples et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For example, recent analysis from the LiGHT trial demonstrated that total SLT power and 2-month IOP were predictors of drop-free disease control at 36 months after single SLT. 30 Moreover, patients who are more medically complex tend to be treated by an ophthalmologist as opposed to an optometrist which should be controlled for when making comparisons between group outcomes. 31…”
Section: Open Accessmentioning
confidence: 99%
“…Selective laser trabeculoplasty (SLT) is the least invasive surgery and the most frequently performed laser surgery procedure for treating POAG, employing low-energy laser beams to microscopically modify the trabecular meshwork TM and improve aqueous drainage [20]. In addition to avoiding adherence and cost issues associated with daily pharmacotherapy, research suggests that patients who initiate treatment with laser procedures show improved IOP lowering [36][37][38]. Data indicate, however, that laser procedures targeting the TM have limited duration and repeatability, particularly with ALT (argon laser trabeculoplasty), as SLT can be repeated.…”
Section: Treatment Optionsmentioning
confidence: 99%